Environmental & Architectural Phenomenology Vol. 33, No. 2 - Kansas State University. Architecture Department (Environmental Architectural Phenomenology, 2022)
Architect Christopher Alexander died in March, and philosopher Robert Mugerauer died in May. This issue of EAP is entirely a memorial to these two significant thinkers whose works were a major contribution to environmental and architectural phenomenology. The issue includes entries from philosopher Ingrid Leman Stefanovic, anthropologist Jenny Quillien, and computer-program researcher and poet Richard Gabriel. We republish several essays and passages from Alexander and Mugerauer’s writings. The issue includes a portfolio of photographs of Alexander’s Eishen Campus in Japan, kindly provided by Japanese photographer Takeshi Kakeda.